1999
DOI: 10.1055/s-0038-1632478
|View full text |Cite
|
Sign up to set email alerts
|

Microangiography of the Humeral Condyle in Cocker Spaniel and Non-Cocker Spaniel Dogs

Abstract: SummaryThe purpose of this study was to evaluate the blood supply to the humeral condyle of dogs and compare the blood supply of Cocker Spaniel dogs to non- Cocker Spaniel dogs. We hypothesize that there is a congenitally altered blood supply of the humeral condyle in some Cocker Spaniels when compared to the blood supply of the humeral condyle in other breeds of dogs, which leads to abnormal ossification between the medial and lateral aspects of the humeral condyle, and predisposes them to fracture and delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…The high complication rate after TCS placement may be the result of continued postoperative instability, placement of the TCS through abnormal or sclerotic bone with decreased capillary density, bone necrosis due to high drill temperatures in sclerotic bone, minimal soft tissue coverage of the lateral aspect of the elbow, repeated trauma of the lateral elbow due to contact with ground when lying down, and presence of a cryptic infection within the intracondylar fissure prior to surgery (S. Carmichael, personal communication, January 2010). Most previous studies have reported persistence of the intracondylar fissure regardless of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The high complication rate after TCS placement may be the result of continued postoperative instability, placement of the TCS through abnormal or sclerotic bone with decreased capillary density, bone necrosis due to high drill temperatures in sclerotic bone, minimal soft tissue coverage of the lateral aspect of the elbow, repeated trauma of the lateral elbow due to contact with ground when lying down, and presence of a cryptic infection within the intracondylar fissure prior to surgery (S. Carmichael, personal communication, January 2010). Most previous studies have reported persistence of the intracondylar fissure regardless of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the higher rate of postoperative sepsis in dogs undergoing surgical management of IOHC is placement of an implant in an area of abnormal and sclerotic bone. One microangiography study demonstrated a decreased density of vessels in the humeral condyle of the cocker spaniel (without IOHC) 24 ; however, the significance of this observation is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Summarily, the overall complication rate after surgery for management of IOHC was 59.5% with the most common complications being development of a seroma (n = 25) or SSI (24). The incidence of SSI was higher than anticipated and this should be discussed with an owner before undertaking surgical management of IOHC.…”
Section: Limitationsmentioning
confidence: 94%
See 2 more Smart Citations